The effect on conception rates of bladder fullness during intrauterine insemination: A retrospective cohort study - Bakacak, Zeyneb (Journal of Surgery and Medicine, 2020)
Aim: Embryo transfer in in-vitro fertilization (IVF) cycles is performed with a full bladder, being careful to avoid surgical instrumentation to the cervix as much as possible, so that uterine contractions are not stimulated. The aim of this study was to investigate whether a full bladder during the application of intrauterine insemination increased pregnancy rates by correcting the cervico-uterine axis, thereby enabling easier access of sperm to the uterine cavity. Methods: This study included 61 patients undergoing IUI procedures, which were performed on patients with infertility since at least one year and those with at least one open oviduct as seen on hysterosalpingography (HSG). Patients’ demographic data, folliculometry measurements, spermiogram parameters, bladder fullness status on abdominal ultrasonography during the application, and beta hGC levels on the 14th day following the application were recorded from the patient files. Results: No statistically significant differences were determined between the two groups in terms of demographic data and folliculometry measurements. The conception rate was 20% in the full bladder group, and 12% in the empty bladder group. Tenaculum application was at a statistically significantly higher rate in the empty bladder group than in the full bladder group (P<0.001). The conception rate was insignificantly higher in the full bladder group (P=0.342). Conclusion: A full bladder facilitates sperm access to the uterine cavity and may increase conception rates. There is a need for further prospective randomized studies with a larger series to obtain better results.